An electrolyte additive and its preparation method and application

By using electrolyte additives containing benzonitrile and phosphoheterocyclic structures in lithium-ion battery electrolyte, the problems of complexity and performance losses of various additives in the prior art are solved, and the long-term cycle stability of the battery is achieved and High safety performance.

CN114744282BActive Publication Date: 2025-02-07SVOLT ENERGY TECH (WUXI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210475995.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-29
Publication Date
2025-02-07
Estimated Expiration
2042-04-29

AI Technical Summary

Technical Problem

The integrated application of multiple additives in existing lithium-ion battery electrolytes will lose battery performance, increase production complexity and cost, and it is difficult to improve cycle life and safety performance at the same time.

Method used

Using an electrolyte additive containing benzonitrile structure and phosphorus-containing heterocyclic structure, the additive forms a stable electrochemical passivation layer when the lithium-ion battery is first charged, which improves the cycle life and distributes phosphorus free radicals in the case of overheating to prevent Battery combustion reaction.

Benefits of technology

It effectively improves the cycle life and safety performance of lithium-ion batteries, has excellent overcharge resistance and high electrochemical windows, ensuring the safety of the battery under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114744282B_ABST
    Figure CN114744282B_ABST
Patent Text Reader

Abstract

The present invention provides an electrolyte additive and a preparation method and application thereof. The structure of the electrolyte additive comprises a benzonitrile structure and a phosphorus-containing heterocyclic structure. The phosphorus-containing heterocyclic structure can improve the cycle life and safety performance of a lithium-ion battery, and the benzonitrile structure can enable the lithium-ion battery to have excellent overcharge resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to an electrolyte additive and a preparation method and application thereof. Background Art

[0002] With the rapid development of renewable energy technology, electric vehicles and portable wearable electronic products, there is an increasing demand for energy storage devices with high specific energy performance. Among various energy storage technologies, lithium-ion batteries dominate due to their high operating voltage and high energy density, but the safety and stability of the electrolytes they use are becoming key issues restricting their rapid development. At present, introducing additives into the electrolyte is an effective strategy to improve the safety and electrochemical performance of lithium-ion batteries. For example, the use of overcharge protectors can delay the thermal runaway of the battery due to overcharging, and flame retardant additives can reduce the hazards caused by thermal runaway of the battery and avoid fire or explosion. In addition, film-forming additives can adjust the interface chemistry between the electrolyte and the electrode to ensure the stability of battery performance.

[0003] CN112375061A discloses an electrolyte film-forming additive, a synthesis method and its application. The additive is mainly a film-forming additive, and its benzene ring and glycerol carbonate group can quickly act on the surface of the negative electrode, improve the interface between the electrolyte and the negative electrode, and quickly form a stable and dense SEI film on the surface of the negative electrode, inhibit electrolyte decomposition, limit the embedding of solvents and other additives into the surface of the negative electrode, prevent the surface of the negative electrode from being damaged, and can improve the cycle performance of the battery and effectively increase the cycle life.

[0004] CN113140794A discloses an electrolyte film-forming additive and a lithium ion battery electrolyte containing the additive. The electrolyte film-forming additive is a silicon-based film-forming additive. The electrolyte film-forming additive has a unique structure. After the negative electrode is immersed in the electrolyte, the carbonyl group is used to form a condensate containing organic silicon flexible functional groups through a self-condensation reaction. The condensate will form a layer of organic silicon flexible functional group protective film with high stability on the surface of the negative electrode material. Since the network condensate has good stability and mechanical toughness, it can better protect the negative electrode material, which is beneficial to improving the charge and discharge cycle and high-temperature storage performance of the lithium ion battery.

[0005] Although the electrolyte additives described in the above scheme can solve certain performance defects of the battery, the integrated application of multiple additives in the electrolyte will not only cause some loss of battery performance, but also increase the complexity and difficulty of electrolyte production. Therefore, under the premise of ensuring battery performance, exploring multifunctional additives for lithium-ion battery electrolytes will help simplify the electrolyte system and reduce manufacturing costs. Summary of the invention

[0006] The object of the present invention is to provide an electrolyte additive and a preparation method and application thereof. The structure of the electrolyte additive of the present invention comprises a benzonitrile structure and a phosphorus-containing heterocyclic structure. The phosphorus-containing heterocyclic structure can improve the cycle life and safety performance of lithium-ion batteries, and the benzonitrile structure can enable lithium-ion batteries to have excellent overcharge resistance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an electrolyte additive, the structural formula of the electrolyte additive is shown in Formula I:

[0009]

[0010] Wherein, R is selected from any one of C1-C5 chain alkylene groups, and X1-X4 are H or halogen.

[0011] The electrolyte additive of the present invention contains a phosphorus heterocyclic structure, which can decompose on the surface of the negative electrode, especially the carbon negative electrode surface, before the carbonate organic solvent during the first charging process of the lithium ion battery to form a stable electrochemical passivation layer, which can prevent the further reduction and decomposition of the electrolyte organic solvent during the subsequent charge and discharge cycle, thereby improving the cycle life of the lithium ion battery. The phosphorus heterocyclic structure can decompose and release phosphorus-containing free radicals when the battery is overheated, and the free radicals have the ability to capture hydrogen free radicals in the battery system, thereby preventing the occurrence of battery electrolyte combustion reactions, and can effectively avoid battery fires and explosions.

[0012] The benzonitrile structure selected in the electrolyte additive of the present invention has a π-π conjugated structure formed by a benzene ring and a cyano group, which has a strong electron-withdrawing ability. The entire electrolyte additive structure has a high resistance to electrochemical oxidation, and the working voltage of the electrolyte prepared therefrom is much greater than the working voltage of conventional positive electrode materials; at the same time, the hydrogen element on the benzene ring structure has a reversible ability to gain and lose electrons due to the substitution of halogens, and has the characteristics of a redox shuttle, which will enable the lithium-ion battery to have excellent overcharge resistance.

[0013] Preferably, the R includes any one of a methylene group, an ethylene group, a n-propylene group or an n-butylene group.

[0014] Preferably, at least one of X1 to X4 is an F element.

[0015] Preferably, the electrolyte additive includes Any one or a combination of at least two of the following.

[0016] In a second aspect, the present invention provides a method for preparing the electrolyte additive as described in the first aspect, the preparation method comprising the following steps:

[0017] (1) mixing hydroxybenzonitrile, triethylamine and a solvent to obtain a mixed solution;

[0018] (2) The mixed solution obtained in step (1) is mixed with a halogenated dioxaphospholane to react to obtain the electrolyte additive.

[0019] Preferably, the molar ratio of hydroxybenzonitrile to triethylamine in step (1) is 1:(1-1.05), for example: 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04 or 1:1.05, etc.

[0020] Preferably, the solvent in step (1) comprises any one of toluene, tetrahydrofuran, N,N-dimethylformamide or acetone, or a combination of at least two thereof.

[0021] Preferably, the mixed solution is placed in an ice water bath.

[0022] Preferably, the molar ratio of the halogenated dioxaphospholane to triethylamine in step (2) is 1:(1-1.05), for example: 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04 or 1:1.05, etc.

[0023] Preferably, stirring is performed during the reaction in step (2).

[0024] Preferably, the reaction time is 24 to 48 hours, for example, 24 hours, 28 hours, 30 hours, 36 hours, 40 hours or 48 hours.

[0025] Preferably, the reaction is followed by filtration, and the clear liquid obtained by filtration is subjected to rotary evaporation to obtain the electrolyte additive.

[0026] In a third aspect, the present invention provides an electrolyte, comprising the electrolyte additive as described in the first aspect, wherein the mass of the electrolyte additive is 0.1 to 10%, for example 0.1%, 0.5%, 1%, 1.5%, 2%, 5% or 10%, etc., preferably 0.5 to 1.5%, based on the mass of the solvent in the electrolyte as 100%.

[0027] In a fourth aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the electrolyte as described in the third aspect.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The structure of the electrolyte additive of the present invention comprises a benzonitrile structure and a phosphorus-containing heterocyclic structure. The phosphorus-containing heterocyclic structure can improve the cycle life and safety performance of the lithium-ion battery, and the benzonitrile structure can enable the lithium-ion battery to have excellent overcharge resistance.

[0030] (2) The electrolyte additive of the present invention can effectively improve the flame retardant properties of the electrolyte, which will greatly improve the safety performance of lithium-ion batteries. In terms of electrochemical performance, the electrolyte configured with the multifunctional additive provided in the present application has an electrochemical window of up to 4.86V, which is much higher than that of conventional electrolyte additives. It can match the commonly used positive electrode materials on the market. At the same time, its excellent antioxidant ability enables lithium-ion batteries to have better overcharge performance, ensuring the safety of lithium-ion batteries under extreme conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the infrared spectrum of the electrolyte additive Ⅰ-Ⅰ prepared in Example 1.

[0032] Figure 2 It is the electrochemical window test curve of the additives described in Example 2 and Comparative Examples 1-3.

[0033] Figure 3 This is the voltammetric cycle curve of the electrolyte described in Application Example 2.

[0034] Figure 4 This is the voltammetric cycle curve of the electrolyte described in Comparative Example 1.

[0035] Figure 5 It is a graph showing the change in discharge capacity retention rate of Application Example 1, Application Example 6 and Application Comparative Example 1 and Application Comparative Example 3 with the number of cycles. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0037] Example 1

[0038] This embodiment provides an electrolyte additive, and the preparation method of the electrolyte additive is as follows:

[0039] (1) Dissolve 0.1 mol of 4-hydroxymethylbenzonitrile and 0.105 mol of triethylamine in 80 ml of tetrahydrofuran to obtain a mixed solution, and place the mixture in an ice water bath;

[0040] (2) 0.1 mol of 2-chloro-2-oxo-1,3,2-dioxaphospholane was dissolved in 40 ml of tetrahydrofuran and slowly added dropwise to the mixed solution in (1), and stirred for reaction for 12 h. After the reaction was completed, the reaction product was filtered, and the obtained clear liquid was evaporated under reduced pressure at 80° C. to obtain a colorless oily electrolyte additive. The structural formula of the electrolyte additive is shown in Formula II:

[0041]

[0042] The infrared spectrum of the electrolyte additive is as follows Figure 1 shown.

[0043] Example 2

[0044] This embodiment provides an electrolyte additive, and the preparation method of the electrolyte additive is as follows:

[0045] (1) Dissolve 0.1 mol of 2-fluoro-4-hydroxymethylbenzonitrile and 0.105 mol of triethylamine in 80 ml of tetrahydrofuran to obtain a mixed solution, and place the mixture in an ice water bath;

[0046] (2) 0.1 mol of 2-chloro-2-oxo-1,3,2-dioxaphospholane was dissolved in 40 ml of tetrahydrofuran and slowly added dropwise to the mixed solution in (1), and stirred for reaction for 24 hours. After the reaction was completed, the reaction product was filtered, and the obtained clear liquid was evaporated under reduced pressure at 80° C. to obtain a colorless oily electrolyte additive, the structural formula of which is shown in Formula I-II:

[0047]

[0048] Example 3

[0049] This embodiment provides an electrolyte additive, and the preparation method of the electrolyte additive is as follows:

[0050] (1) Dissolve 0.1 mol of 2,6-difluoro-4-hydroxymethylbenzonitrile and 0.105 mol of triethylamine in 80 ml of tetrahydrofuran to obtain a mixed solution, and place the mixture in an ice water bath;

[0051] (2) 0.1 mol of 2-chloro-2-oxo-1,3,2-dioxaphospholane was dissolved in 40 ml of tetrahydrofuran and slowly added dropwise to the mixed solution in (1), and stirred for reaction for 24 hours. After the reaction was completed, the reaction product was filtered, and the obtained clear liquid was subjected to reduced pressure rotary evaporation at 80° C. to obtain a colorless oily electrolyte additive, the structural formula of which is shown in Formula I-III:

[0052]

[0053] Example 4

[0054] This embodiment provides an electrolyte additive, and the preparation method of the electrolyte additive is as follows:

[0055] (1) Dissolve 0.1 mol of 2,3,6-trifluoro-4-hydroxymethylbenzonitrile and 0.105 mol of triethylamine in 80 ml of tetrahydrofuran to obtain a mixed solution, and place the mixture in an ice water bath;

[0056] (2) 0.1 mol of 2-chloro-2-oxo-1,3,2-dioxaphospholane was dissolved in 40 ml of tetrahydrofuran and slowly added dropwise to the mixed solution in (1), and stirred for reaction for 24 hours. After the reaction was completed, the reaction product was filtered, and the obtained clear liquid was evaporated under reduced pressure at 80° C. to obtain a colorless oily electrolyte electrolyte additive, the structural formula of which is shown in Formula I-IV:

[0057]

[0058] Example 5

[0059] This embodiment provides an electrolyte additive, and the preparation method of the electrolyte additive is as follows:

[0060] (1) Dissolve 0.1 mol of 2,3,5,6-tetrafluoro-4-hydroxymethylbenzonitrile and 0.105 mol of triethylamine in 80 ml of tetrahydrofuran to obtain a mixed solution, and place the mixture in an ice water bath;

[0061] (2) 0.1 mol of 2-chloro-2-oxo-1,3,2-dioxaphospholane was dissolved in 40 ml of tetrahydrofuran and slowly added dropwise to the mixed solution in (1), and stirred for reaction for 24 hours. After the reaction was completed, the reaction product was filtered, and the obtained clear liquid was evaporated under reduced pressure at 80° C. to obtain a colorless oily electrolyte additive, the structural formula of which is shown in Formula I-V:

[0062]

[0063] Comparative Example 1

[0064] In this comparative example, fluoroethylene carbonate is used as an electrolyte additive, and the structural formula of the fluoroethylene carbonate is shown in Formula II-I:

[0065]

[0066] Comparative Example 2

[0067] In this comparative example, fluoroethylene carbonate is used as an electrolyte additive, and the structural formula of the fluoroethylene carbonate is shown in Formula II-II:

[0068]

[0069] Comparative Example 3

[0070] In this comparative example, fluoroethylene carbonate is used as an electrolyte additive, and the structural formula of the fluoroethylene carbonate is shown in Formula II-III:

[0071]

[0072] Application Example 1

[0073] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and 0.5% of the total mass of the organic solvent was added as electrolyte additive Ⅰ-Ⅰ, and lithium hexafluorophosphate was used as the lithium salt at a concentration of 1 mol / L.

[0074] Application Example 2

[0075] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and electrolyte additives I-II were added at a total weight of 0.5% of the organic solvent, and lithium hexafluorophosphate was used as the lithium salt at a concentration of 1 mol / L.

[0076] Application Example 3

[0077] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and electrolyte additives I-II were added at a total weight of 0.5% of the organic solvent, and lithium hexafluorophosphate was used as the lithium salt at a concentration of 1 mol / L.

[0078] Application Example 4

[0079] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 are mixed, and electrolyte additives I-IV are added at a total weight of 0.5% of the organic solvent, and lithium hexafluorophosphate is used as the lithium salt at a concentration of 1 mol / L.

[0080] Application Example 5

[0081] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and electrolyte additives I-V were added at a total weight of 0.5% of the organic solvent, and lithium hexafluorophosphate was used as the lithium salt at a concentration of 1 mol / L.

[0082] Application Example 6

[0083] The only difference between this application example and application example 1 is that the amount of the electrolyte additive added is 0.1% of the mass of the organic solvent, and the other conditions and parameters are exactly the same as those in application example 1.

[0084] Application Example 7

[0085] The only difference between this application example and application example 1 is that the amount of the electrolyte additive added is 0.3% of the mass of the organic solvent, and the other conditions and parameters are exactly the same as those in application example 1.

[0086] Application Example 8

[0087] The only difference between this application example and application example 1 is that the amount of the electrolyte additive added is 1.0% of the mass of the organic solvent, and the other conditions and parameters are exactly the same as those in application example 1.

[0088] Application Comparative Example 1

[0089] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and electrolyte additives II-I were added at a total weight of 0.5% of the organic solvent, with lithium hexafluorophosphate as the lithium salt at a concentration of 1 mol / L.

[0090] Application Comparative Example 2

[0091] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and electrolyte additives II-II were added at a total weight of 0.5% of the organic solvent, and lithium hexafluorophosphate was used as the lithium salt at a concentration of 1 mol / L.

[0092] Application Comparative Example 3

[0093] Under anhydrous and oxygen-free conditions, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate organic solvents in a volume ratio of 2:4:4 were mixed, and electrolyte additives II-III were added at a total weight of 0.5% of the organic solvent, and lithium hexafluorophosphate was used as the lithium salt at a concentration of 1 mol / L.

[0094] Performance Test:

[0095] The electrolytes configured for the corresponding use cases 1-8 and the comparative examples 1-3 were tested as follows:

[0096] ① Flame retardant performance (self-extinguishing time): Use a glass wool ball with a diameter of 5 mm to absorb 1 g of electrolyte, ignite it with an ignition gun (flame temperature 400°C), and record the time taken by the glass wool ball adsorbing the electrolyte from combustion to extinguishing. Repeat the test 5 times for each electrolyte, take the average value, and record it as the SET value. The test results are shown in Table 1.

[0097] ② Electrochemical window: A lithium metal sheet was used as an electrode, a stainless steel sheet was used as a counter electrode, and a commercial diaphragm was selected to assemble a 2032-type button cell. The cell was left to stand for 12 hours. The voltage scanning rate in the button cell test was 0.1 mV / s, and the scanning voltage was from 0 V to 6 V. The test results are shown in Table 1. The electrochemical window test curves of Example 2 and Comparative Examples 1-3 are shown in Table 1. Figure 2 shown.

[0098] The electrolytes configured in Examples 1-7 and Comparative Examples 1-3 were used to assemble lithium-ion batteries: the positive electrode was prepared with lithium nickel cobalt manganese oxide (NCM811) as the active material, the negative electrode was prepared with graphite as the active material, and the diaphragm was prepared with a commercial diaphragm. The lithium-ion batteries were obtained by lamination, packaging, injection, and formation assembly, and left to stand for 48 hours, and the following tests were performed:

[0099] ③ Initial charge and discharge efficiency: Charge at 0.1C constant current to the termination voltage, then switch the termination voltage to constant voltage charging until the charging current drops to 0.05C and stop charging, record the initial charge capacity; let stand for 30 minutes, discharge at 0.1C constant current to the termination voltage and stop discharging, record the initial discharge capacity. The ratio of initial discharge capacity to initial charge capacity is taken as the initial charge and discharge efficiency, and the test results are shown in Table 1.

[0100] ④ Cycle performance (at 25°C): 1) Discharge at 1C constant current until the end voltage is reached and then stand for 30 minutes;

[0101] 2) Charge at a constant current of 1C until the termination voltage is switched to constant voltage charging until the charging current drops to 0.05C and stop charging, and let it stand for 30 minutes; 3) Discharge at a constant current of 1C until the termination voltage is stopped, let it stand for 30 minutes, and record the discharge capacity; 4) Cycle continuously for 400 times according to 2) to 3), and take the ratio of the 400 discharge capacity to the first discharge capacity as the discharge capacity retention rate. The test results are shown in Table 1, and the discharge capacity retention rate of Application Example 1, Application Example 6 and Application Comparative Example 1 and Application Comparative Example 3 as a function of the number of cycles is shown in Table 1. Figure 5 shown.

[0102] ⑤ Overcharge performance: Charge at a constant current of 0.33C to the termination voltage and then switch to constant voltage charging until the charging current drops to 0.05C and then stop charging. Then charge at a current of 1C to 1.1 times the termination voltage or 115% SOC of the battery and then stop charging. Stand and observe for 1 hour. The results are shown in Table 1:

[0103] Table 1

[0104]

[0105]

[0106] As can be seen from Table 1, by comparing Application Examples 1-8 with Application Comparative Examples 1-3, the electrolyte additive of the present invention can effectively improve the flame retardancy of the electrolyte, which will greatly improve the safety performance of lithium-ion batteries; in terms of electrochemical performance, the electrochemical window of the electrolyte configured with the multifunctional auxiliary agent provided in this application can reach up to 4.86 V, which is much higher than that of conventional electrolyte additives. It can match the currently commonly used ternary nickel cobalt manganese or quaternary nickel cobalt manganese aluminum or cobalt-free (LiNi x Mn y O2, 0 < x, y < 1) cathode materials and graphite + silicon oxide (SiOx, 0 < x < 1) anode materials (the mass ratio of silicon oxide in the anode active material is 0.1-10%). At the same time, its excellent antioxidant ability enables lithium-ion batteries to have good overcharge performance, ensuring the safety of lithium-ion batteries under extreme conditions.

[0107] By comparing Application Example 1 with Application Examples 6-8, it can be obtained that the addition amount of the electrolyte additive of the present invention in the electrolyte will affect the performance of the prepared battery. Controlling the mass of the electrolyte additive at 0.5-1.5% of the solvent in the electrolyte can obtain better battery performance. If the addition amount of the electrolyte additive is too much, it will significantly affect the solvation ability of the organic solvent, reduce the ionic conductivity of the electrolyte, and at the same time, the degree of side reactions inside the lithium-ion battery will intensify, and the battery cannot exhibit its best performance; if the addition amount of the electrolyte additive is too little, it cannot effectively improve the performance of the electrolyte as a whole, especially in terms of the flame retardancy of the electrolyte and the electrochemical window of high voltage resistance.

[0108] ⑥ Cyclic voltammetry curve: Prepare a pole piece with graphite as the active substance, use a lithium metal sheet as the counter electrode, select a commercial separator as the separator, assemble a 2032-type button battery, and let it stand for 12 h. The scanning speed of the voltage in the button battery test is 0.1 mV / s, the scanning range is 0-3 V, and it is scanned cyclically for 4 circles. The cyclic voltammetry curve of the electrolyte of Application Example 2 is as Figure 3 shown, and the cyclic voltammetry curve of the electrolyte of Application Comparative Example 1 is as Figure 4 shown. From Figure 3-4 the comparison, it can be obtained that the electrolyte additive of the present invention can form a stable protective layer on the negative electrode side during the first charge and discharge process, while the commonly used fluoroethylene carbonate film-forming additive in Comparative Example 1 requires 3-4 charge and discharge cycles to achieve a stable effect. The better stability in electrochemistry enables the lithium-ion battery to still exhibit a discharge capacity retention rate of more than 92% after 400 cycles.

[0109] In summary, using the electrolyte additive of the present invention to configure the electrolyte can effectively improve the electrochemical stability of lithium-ion batteries, and at the same time enable lithium-ion batteries to have excellent safety performance and long-term cycle stability.

[0110] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An electrolyte additive, characterized in that: The structural formula of the electrolyte additive is shown in Formula I: Wherein, R is selected from any one of the chain alkylene groups of C1 to C5, and at least one of X1 to X4 is an F element.

2. The electrolyte additive according to claim 1, characterized in that The R includes any one of a methylene group, an ethylene group, a n-propylene group or a n-butylene group.

3. The electrolyte additive according to claim 1 or 2, characterized in that: The electrolyte additive includes Any one or a combination of at least two of the following.

4. A method for preparing the electrolyte additive according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing hydroxybenzonitrile, triethylamine and a solvent to obtain a mixed solution; (2) The mixed solution obtained in step (1) is mixed with a halogenated dioxaphospholane to react to obtain the electrolyte additive.

5. The preparation method according to claim 4, characterized in that: The molar ratio of hydroxybenzonitrile to triethylamine in step (1) is 1:(1-1.05).

6. The preparation method according to claim 4, characterized in that: The solvent in step (1) includes any one of toluene, tetrahydrofuran, N,N-dimethylformamide or acetone, or a combination of at least two thereof.

7. The preparation method according to claim 4, characterized in that: The mixed solution in step (1) is placed in an ice water bath.

8. The preparation method according to claim 4, characterized in that: The molar ratio of the halogenated dioxaphospholane to triethylamine in step (2) is 1:(1-1.05).

9. The preparation method according to claim 4, characterized in that: Stirring is performed during the reaction in step (2).

10. The preparation method according to claim 4, characterized in that: The reaction time of step (2) is 24 to 48 hours.

11. The preparation method according to claim 4, characterized in that: After the reaction in step (2), the reaction is performed by filtering, and the clear liquid obtained by filtration is subjected to rotary evaporation to obtain the electrolyte additive.

12. An electrolyte, characterized in that: The electrolyte comprises the electrolyte additive according to any one of claims 1 to 3, and the mass of the electrolyte additive is 0.1 to 10% based on the mass of the solvent in the electrolyte being 100%.

13. The electrolyte according to claim 12, characterized in that The mass of the electrolyte additive is 0.5-1.5%.

14. A lithium ion battery, characterized in that: The lithium-ion battery comprises the electrolyte according to claim 12.

Citation Information

Patent Citations

  • Electrolyte film-forming additive and synthesis method and application thereof

    CN112375061A

  • Electrolyte film-forming additive and lithium ion battery electrolyte containing additive

    CN113140794A

  • Flame-retardant additive, preparation method therefor and application of flame-retardant additive

    CN110590848A